One-dimensional inverse power reflectionless potentials V(x) = const│x-x₀ │⁻ⁿ - Maydanyuk, S.P. (Вопросы атомной науки и техники, 2004)
A condition, at which inverse power one-dimensional potential becomes reflectionless during propagation through it of a plane wave, is obtained on the basis of SUSY QM methods. A scattering of a particle on spherically symmetric potential is analysed with taking into account of the reflectionless possibility. На основі методів SUSY QM отримано умову, при якій обернено степеневий потенціал стає абсолютно прозорим при проходженні крізь його плоскої хвилі. Представлено аналіз розсіювання частинки на сферично- симетричному потенціалі з врахуванням можливості абсолютної прозорості. С помощью методов SUSY QM получено условие, при котором обратно степенной потенциал становится абсолютно прозрачным при прохождении через него плоской волны. Представлен анализ рассеяния частицы на сферически-симметричном потенциале с учетом возможности абсолютной прозрачности.